The Practice of Belis in Noble Marriages of the Ende Tribe from a Human Rights Perspective - Anjani, Alifiya Rizky; Yuliatin, Yuliatin; Basariah, Basariah; Zubair, Muh. (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to determine the process of implementing Belis at the marriage of Ende Tribe nobility and Belis at the marriage of Ende Tribe nobility from a human rights perspective. This study uses a qualitative research type with a case study research approach. The results of the study indicate that the Belis procession at the marriage of Ende Tribe nobility consists of an initial procession, namely Mbe'o Nia (getting to know the face), Temba Zaza (introduction and confirmation), Ngambe (sitting), Nai Ono and Buku Pelulu (entering, asking and delivering), Bhaze Duza (returning to the tray), Wa'u Sodho (going out to inform), Mbe'o Sa'o (getting to know the house), Minu Ae Petu (drinking hot water), and the core procession, namely Mendhi Belanja (delivering shopping or Belis) and Belis at the marriage of Ende Tribe nobility consists of two types, namely money and cows. Belis in the marriage of the Ende Tribe nobility is in line with Human Rights because Belis is used as part of an effort to respect a person's rights and maintain the relationship between husband and wife so that divorce does not occur, positioning it as something sacred, which to fulfill it requires preparation both materially, mentally, and morally. On the other hand, Belis also contains elements of restrictions and even violations of human rights because in Belis there are elements of restrictions related to the right to marry, form a family and continue offspring through a legal marriage. Then, there is an element of discrimination against groups.